Analisis Kepuasan Pengguna Aplikasi PLN Mobile di Kota Palembang dengan Metode EUCS - Fransiska Prihatini Sihotang (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The PLN Mobile application was created to make it easier for people to access services from anywhere. This application has been increasingly used since the Covid-19 pandemic. To find whether the user is satisfied with the application or not, it is necessary to do an analysis. The results can be used for further application development. On this occasion, the analysis uses the End User Computing Satisfaction (EUCS) method. This study aims to determine whether the five factors possessed by EUCS (content, accuracy, format, ease of use, and timeliness) influence the satisfaction of PLN Mobile application users in Palembang City. The research sample used is PLN Mobile users in Palembang City. Analysis of data from the questionnaire results using SPSS shows that the five EUCS variables both partially and simultaneously have a positive and significant effect on user satisfaction with the PLN Mobile application.